Theoretical Foundations for Integrating Sustainable Development Goals into Geography Education: UNESCO’s Whole-School Approach - Aidana Abu (Modern Scientific Technology, 2025)
The growing complexity of global environmental, social, and economic challenges has intensified the need to integrate Sustainable Development Goals (SDGs) into formal education systems. Geography education, due to its interdisciplinary nature and strong spatial orientation, plays a crucial role in promoting sustainability literacy and global citizenship. This theoretical article explores the foundations of integrating SDGs into geography education through UNESCO’s Whole-School Approach. Drawing on Education for Sustainable Development (ESD), systems thinking, transformative learning theory, and competency-based education, the study conceptualizes a holistic framework for embedding sustainability across curriculum, pedagogy, school culture, and community engagement. The article provides a theoretical basis for the development of an SDG School Mapping Model adapted to geography education in Kazakhstan